GIS for Water Resource and Watershed Management - Lyon, John (CRC Press, 2009)
The use of GIS, and its application for solving environmental problems is growing rapidly. This powerful set of tools can be used to great effect in hydrological modeling, environment and habitat assessments, ecosystem studies, monitoring of wetlands and forested watersheds, urban studies, agricultural impact assessment and much more. GIS for Watershed and Water Resource Management explains the fundamentals, demonstrates new approaches, techniques and methods, and provides examples of real applications. It presents the basic concepts, and shows how to acquire the critical information needed to plan and implement GIS studies, and develop practical solutions for environmental management and problem solving.